Safety of baricitinib for the treatment of rheumatoid arthritis over a median of 4.6 and up to 9.3 years of treatment: final results from long-term extension study and integrated database. Issue 3 (27th October 2021) - Taylor, Peter C; Takeuchi, Tsutomu; Burmester, Gerd R; Durez, Patrick; Smolen, Josef S; Deberdt, Walter; Issa, Maher; Terres, Jorge Ross; Bello, Natalia; Winthrop, Kevin L
Abstract : Objective: To report long-term safety from the completed extension trial of baricitinib, an oral selective Janus kinase inhibitor, in patients with active rheumatoid arthritis (RA). Methods: Treatment-emergent adverse events are summarised from an integrated database (9 phase III/II/Ib and 1 long-term extension) of patients who received any baricitinib dose (All-bari-RA). Standardised incidence ratio (SIR) for malignancy (excluding non-melanoma skin cancer (NMSC)) and standardised mortality ratio (SMR) were estimated. Additional analysis was done in a subset of patients who had ever taken 2 mg or 4 mg baricitinib. Results: 3770 patients received baricitinib (14 744 patient-years of exposure (PYE)). All-bari-RA incidence rates (IRs) per 100 patient-years at risk were 2.6, 3.0 and 0.5 for serious infections, herpes zoster and major adverse cardiovascular events (MACE), respectively. In patients aged ≥50 with ≥1 cardiovascular risk factor, the IR for MACE was 0.77 (95% CI 0.56 to 1.04). The IR for malignancy (excluding NMSC) during the first 48 weeks was 0.6 and remained stable thereafter (IR 1.0). The SIR for malignancies excluding NMSC was 1.07 (95% CI 0.90 to 1.26) and the SMR was 0.74 (95% CI 0.59 to 0.92). All-bari-RA IRs for deep vein thrombosis (DVT)/pulmonary embolism (PE), DVT and PE were 0.5 (95% CI 0.38 to 0.61), 0.4 (95% CI 0.26 to 0.45) and 0.3 (95% CI 0.18 to 0.35), respectively. No clear dose differences were noted for exposure-adjusted IRs (per 100 PYE) for deaths, serious infections, DVT/PE and MACE. Conclusions: In this integrated analysis including long-term data of baricitinib from 3770 patients (median 4.6 years, up to 9.3 years) with active RA, baricitinib maintained a similar safety profile to earlier analyses. No new safety signals were identified. Trial registration number: NCT01185353, NCT00902486, NCT01469013, NCT01710358, NCT02265705, NCT01721044, NCT01721057, NCT01711359 and NCT01885078 .